2018
DOI: 10.1186/s12913-018-3084-z
|View full text |Cite|
|
Sign up to set email alerts
|

Does specialist physician supply affect pediatric asthma health outcomes?

Abstract: BackgroundPediatrician and pediatric subspecialist density varies substantially among the various Canadian provinces, as well as among various states in the US. It is unknown whether this variability impacts health outcomes. To study this knowledge gap, we evaluated pediatric asthma admission rates within the 2 Canadian provinces of Manitoba and Saskatchewan, which have similarly sized pediatric populations and substantially different physician densities.MethodsThis was a retrospective cross-sectional cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Nonetheless, these data are supported by a retrospective, cross-sectional study from Canada that demonstrated a strong connection between the lack of asthma specialists and hospital admissions of children with asthma. 10 Childhood asthma is a heterogeneous condition with wide variability among patients. 16 It is reasonable to assume that not all patients who meet with a specialist will benefit directly from a single encounter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, these data are supported by a retrospective, cross-sectional study from Canada that demonstrated a strong connection between the lack of asthma specialists and hospital admissions of children with asthma. 10 Childhood asthma is a heterogeneous condition with wide variability among patients. 16 It is reasonable to assume that not all patients who meet with a specialist will benefit directly from a single encounter.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Although recommended for children, the effect of asthma specialists' intervention on asthma control in the pediatric population is much less explored. [9][10][11] The current study evaluated the effect of asthma specialists' intervention on asthma control, in a large group of Israeli children.…”
Section: Introductionmentioning
confidence: 99%
“…In the original publication of this article [1], the institutional author’s name needs to be revised from The Paediatric Chairs of Canada Mark Bernstein to The Paediatric Chairs of Canada.…”
mentioning
confidence: 99%